Brazilian perspectives on Italian cinema: Perspectives for interfaces between literature, history, and audiovisual in the context of telecollaboration - Betella, Gabriela Kvacek [UNESP] (Springer Nature, 2023)
In the scope of learning foreign language and culture, the cultural dimension is a determining factor for the success of communicative situations. We resort to the field of intercultural communication by Edward Hall and Milton Bennett, stressing skills linked to motivation, respect, and effective attitudes in communication among different cultures, at the expense of high level of linguistic proficiency without the perception and understanding of identities. We consider skills and knowledge of the intercultural speaker according to Michael Byram, Bella Gribkova, and Hugh Starkey, and finally, to align these starting factors in research aimed at improving telecollaboration networks, we turn to Aurora Castillo-Scott. Although this work does not bring research results with synchronous telecollaboration, as it is qualitative, the benefits of the study are linked to the substrates for a productive interaction emerging from stimulated interests, even from an artistic and social perspective. The increase in the ability to interpret literary texts and the growth in the understanding of scenes from foreign films may occur at the same time as linguistic structures are acquired. We present subsidies for exploring Italian language, literature, and cinema through the immanent analysis of films by the Italian filmmaker Gianni Amelio adapted from literary works.
Keywords: Contemporary Italian cinema; Contemporary Italian literature; Intercultural communication; Teaching of foreign language and culture